Differentiated chondrosarcoma, originated in thyroid cartilage of larynx: evaluation and treatment. Clinical case presentation - Pocius, Linas; Čepulis, Vytautas (Acta medica Lituanica, 2013)
Background. The goal of our clinical case presentation is to introduce evaluation and treatment of rare head and neck tumor, the laryngeal chondrosarcoma (CS). Despite disease origin being properly suspected at the early management of our patient, the final outcomes tend to be just satisfactory because too many cofactors have had a strong influence on the course of disease. Materials and methods. In this case, we described applied investigations and chosen tactics of treatment to our patient in a chronological manner, some immediate results, but also remote consequences of the management of this disease. Results. In our opinion, outcome in this patient’s case was predicted not just by the biology of malignancy itself, but also by some specific qualities of the tumor and even misinterpretations of instrumental examination at the moment of making decisions regarding the initial treatment; moreover, some solutions, corrected by the patient himself, maybe played an important role in the clinical course further. We want to point out how achieved results and outcomes could be unpredictable, under influence of near coincidence of fate, and different, in comparison with the cases described in the majority of the literature. Conclusions. 1. Relatively simple diagnostic with contemporary features, plenty of modern surgical treatment possibilities or even combined therapy in complicated cases – it makes no difficulties for management of typical chondrosarcoma of the larynx, yet sometimes tricky findings when evaluating the disease and an unpredictable or surprising course of treatment and continuation make this rare kind of head and neck malignancies really special. 2. RT neither chemotherapy are recommended therapeutic options, except some rare individual cases. 3. Conservative surgery tends to be adequate if made properly and in time, it obviously ensures long-term remission or cancer-free life.